Analysing Peri-implant Stress on Crestal Bone: A Three-Dimensional Finite Element Analysis of Various Abutment Diameters - Anupama Aradya; Ramesh Chowdhary; Ganesh S; Sowmya H K; Koduru Sravani; Narahari Ranganatha (Medical Research and Its Applications Vol. 8, 2024)
Aim: This study aims to investigate the impact of platform switching on the trans-cortical section of bone adjacent to an endosseous dental implant in the posterior mandible region, under vertical and oblique forces. Materials and Methods: Three-dimensional finite element models were constructed using ANSYS 13.0 software, employing Type II mandibular bone with cortical thickness ranging from 0.595 mm to 1.515 mm, encompassing a crestal region of 1.5 mm surrounding dense trabecular bone. The implant design featured a 5 mm restorative platform tapering down to 4.5 mm wide at the threads, with a length of 13 mm and an abutment height of 3 mm. Two scenarios were modeled: 1. An implant with a 5 mm diameter abutment representing a standard platform, and 2. An implant with a 4.5 mm diameter abutment representing platform switching. Vertical and oblique forces, simulating masticatory loads, were applied at 100 N and 15 degrees from the vertical axis, respectively. Von-Mises stress analysis was conducted. Results: Under oblique forces, cortical stress in the conventional and platform switching models measured 59.329 MPa and 39.952 MPa, respectively. For vertical forces, cortical stress in the conventional and platform switching models was 13.914 MPa and 12.793 MPa, respectively. With a wider implant in the platform switching, a lower incidence of stress was found that was also concentrated away from the peri-implant bone surface which would cause less microdamage in the bone tissue, resulting in minimal crestal bone loss. Conclusion: The study demonstrates that reducing abutment diameter (i.e., platform switching) leads to a measurable decrease in Von-Mises stress within the crestal region of cortical bone.